2021
DOI: 10.26466/opus.837465
|View full text |Cite
|
Sign up to set email alerts
|

Bilgisayar Destekli Matematik Eğitimi Alanında 2015-2019 Yılları Arasında Yapılan Araştırmaların İncelenmesi

Abstract: Computer assisted instruction is one of most applied methods in mathematics education In this study, a systematic literature review was conducted in the field of Computer Assisted Mathematics Instruction to reveal the recent tendency by examining the articles of journals originated in Turkey between 2015 and 2019. At the end of the two-phased selection method, 39 articles were reviewed in the current study. Demographic and methodological characteristics of articles as well as their topics and the applied techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(21 reference statements)
0
1
0
3
Order By: Relevance
“…Özellikle dinamik matematik yazılımı olan Geogebra ile geometri yazılımları olan Cabri 3D/II ile Sketchpad öğrenme araçları araştırmacılar tarafından daha fazla tercih edilmiştir. Bu sonuç, alanyazındaki benzer yönde yapılan sistematik tarama bulguları ile uyumluluk göstermektedir (Aldemir ve Tatar, 2014;Battal ve Çalışkan, 2021;Bayram, 2019;Tabuk, 2019). Özellikle matematik konu ve kavramlarının öğretilmesinde işlevsel ve verimli bir öğrenme ortamı sunan Geogebra yazılımının birçok çalışmada yer alması çalışmanın dikkat çekici bulgularındandır.…”
Section: Nicel Betimsel Nicel Kestirimsel Nitelunclassified
See 2 more Smart Citations
“…Özellikle dinamik matematik yazılımı olan Geogebra ile geometri yazılımları olan Cabri 3D/II ile Sketchpad öğrenme araçları araştırmacılar tarafından daha fazla tercih edilmiştir. Bu sonuç, alanyazındaki benzer yönde yapılan sistematik tarama bulguları ile uyumluluk göstermektedir (Aldemir ve Tatar, 2014;Battal ve Çalışkan, 2021;Bayram, 2019;Tabuk, 2019). Özellikle matematik konu ve kavramlarının öğretilmesinde işlevsel ve verimli bir öğrenme ortamı sunan Geogebra yazılımının birçok çalışmada yer alması çalışmanın dikkat çekici bulgularındandır.…”
Section: Nicel Betimsel Nicel Kestirimsel Nitelunclassified
“…Bu bakımdan matematiksel kavramların öğrenciler tarafından anlamlandırılmasını desteklemenin etkili yollardan biri de matematik eğitimine teknolojiyi etkili bir şekilde entegre edebilmektir (İnce-Muslu ve Erduran, 2020). Türkiye'de matematik eğitimi alanında teknoloji destekli uygulama içeriklerini konu edinen araştırmalar genel olarak irdelendiğinde, son yıllarda teknolojinin öğrenme ortamlarında daha fazla yer aldığı ve bu yönde artan bir ilginin olduğu görülmektedir (Battal ve Çalışkan, 2021;Şimşek ve Yaşar, 2019;Tatar ve diğer., 2013). Örneğin Tatar ve diğer.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…While studies reveal the positive effects of technology use in education (Byun & Joung, 2018), this situation continues in mathematics teaching; studies that concluded that the use of technology in mathematics teaching has positive effects (Battal & Çalışkan, 2021;Kutluca et al, 2016). The use of technology in mathematics education is associated with achievement (Akbaş, 2019;Çetin & Mirasyedioğlu, 2019), motivation (Nguyen et al, 2006) attitude (Nguyen et al, 2006), and self-efficacy (Mistretta, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The method in which computer software that uses elements such as pictures, audio, and video and contributes to the concretization of concepts by using them in learning and teaching activities is defined as "Computer Aided Instruction" (CAI). Oğuz, 2007, Battali andÇalışkan, 2021;Demircioğlu and Geban, 1996). The CAI method has come to the fore in recent years as it allows students to repeat, makes subjects easier for students to remember, draws attention, helps students find examples from daily life, and concretize concepts (Akçay, Tüysüz, Feyzioğlu and Oğuz, 2008).…”
Section: Introductionmentioning
confidence: 99%